If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 + 2m = 6(2n + 6) Reorder the terms: -11 + 2m = 6(6 + 2n) -11 + 2m = (6 * 6 + 2n * 6) -11 + 2m = (36 + 12n) Solving -11 + 2m = 36 + 12n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 2m = 36 + 11 + 12n Combine like terms: -11 + 11 = 0 0 + 2m = 36 + 11 + 12n 2m = 36 + 11 + 12n Combine like terms: 36 + 11 = 47 2m = 47 + 12n Divide each side by '2'. m = 23.5 + 6n Simplifying m = 23.5 + 6n
| 9x-9-x=9-x | | 2x+8+9=2x+8 | | 12-2x+4=4 | | x^3-19x^2+90x+52=0 | | 3k-10=12 | | x-4-x+5-3x=4 | | 8(4-7a)=32+8a | | 2x-4-8-6=4x | | x^2+343= | | 5x+8x-10=6x+4 | | 4n^2+3n+6=0 | | 50-.52x=20 | | 1/5x/1/5=9/1/5 | | 2x+4=x-4 | | 3(2w-1)=9(w+3) | | 3x-28=20+7x | | ln(43)=x | | 8-9=x+3+x | | (2+4x)-(x-9)=26 | | 6.8=h | | 6+2x+11=x+13 | | 4-5x+6=4x-8 | | 143=13x+52 | | 6(-2)+4=10 | | 9+x+6=93 | | 7v+26=0 | | 9m-25=35-m | | -1(1*9+5)= | | y-5y=9-3 | | 8y+3(y-2)=5(y+1)-4 | | -4=x^2-3x-4 | | 0.5*2-3*2+5= |